Pengaruh Exercised Responsibility, Pengalaman, Otonomi, Ambiguitas Peran Dan Pendidikan Berkelanjutan Terhadap Kinerja Auditor: (Studi Empiris Pada Bpk Dan Bpkp Perwakilan Propinsi Maluku) - Juliana Kesaulya; Nicodemus Rahabeat (P3M Politeknik Negeri Ambon, 2024)
This study aims to investigate the influence exercised responsibility experience, autonomy, role ambiguity and continuing education on the performance of auditors in BPK and BPKP Representative Maluku.Pengumpulan province this data is done with the direct distribution method that is the way to approach directly the object of research to submit a questionnaire and collect them again that addressed to the auditor BPK and BPKP Representative Maluku Province. With the number of samples used in this study were 60 respondents from the BPK and BPKP Representative Maluku Province. In this study, the sampling technique using a convenience sampling method.Data analysis method used in this research is to test the validity, reliability test and classical assumption, as well as the testing is done by using multiple regression linerar.These results indicate that simultaneously exercised Responsibility, experience, autonomy, role ambiguity and continuing education significant positive effect on the performance of auditor.Secara parisal Responsibility and autonomy exercised significant positive effect on the performance of auditors. Keywords: exercised responsibility, experience, autonomy, role ambiguity and continuing education, the performance auditor.